1998
DOI: 10.1099/0022-1317-79-8-1879
|View full text |Cite
|
Sign up to set email alerts
|

Expression of target genes by coinfection with replication-deficient viral vectors.

Abstract: An in vivo transcription system was developed by coinfection of cells with replication-deficient viral vectors. Recombinant baculovirus (AcT7HCVLuc) and fowlpox virus (FPVT7HCVLuc) carrying a cDNA of the hepatitis C virus (HCV) minigene encoding the HCV 5h untranslated region (UTR), a luciferase gene and the 3h UTR, including the 98 nt extra sequence, under the control of the T7 promoter were constructed. The HCV minigene was synthesized in various cells by coinfection with one of these two viruses and recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In pT7HCV07Luc, the luciferase gene was connected in frame to the coding region of two-thirds of the core protein. pHCV09Luc, which has been described previously (61), has nt 1 to 924 of the HCV cDNA, the luciferase gene, cDNA for the coding region of the C terminus of NS5B and the 3ЈUTR of HCV, a ribozyme of hepatitis D virus, and a T7 terminator under the T7 promoter. In this plasmid, the luciferase gene was connected in frame to the E1 coding gene.…”
Section: Cellsmentioning
confidence: 99%
“…In pT7HCV07Luc, the luciferase gene was connected in frame to the coding region of two-thirds of the core protein. pHCV09Luc, which has been described previously (61), has nt 1 to 924 of the HCV cDNA, the luciferase gene, cDNA for the coding region of the C terminus of NS5B and the 3ЈUTR of HCV, a ribozyme of hepatitis D virus, and a T7 terminator under the T7 promoter. In this plasmid, the luciferase gene was connected in frame to the E1 coding gene.…”
Section: Cellsmentioning
confidence: 99%
“…However, it is suggested that the transduction block lies not in the endosomal escape, but in the cytoplasmic trafficking or nuclear import of the virus capsids WI38 [21] MRC5 [132,147] ECV-304 [113] HUVEC [148] PC3 (prostate cancer) [149] Osteosarcoma SAOS-2 [21,150] Glioma cells [45] Pancreatic cells [151] Keratinocytes [21] Bone marrow fibroblast [21] Primary foreskin fibroblast [152] Primary neural cells [115] Primary hepatocytes [7,8] Coronary smooth muscle cells and coronary endothelial cells [12] Mesenchymal stem cells [14] Embryonic stem cells [16] Non-human primate cells COS-7 [21,30] Vero [109] CV-1 [20] Porcine cells CPK [119] FS-L3 [9] coronary smooth muscle cell [12] Bovine cells…”
Section: A Mechanismsmentioning
confidence: 99%
“…Yap and colleagues [46] reported the use of a two baculovirus system to recover high-titer polio virus from cDNA. [50][51][52] For example, baculovirus HBV chimeras were used to evaluate the antiviral properties of a nucleoside analog (lamivudine) on HBVreplication in HepG2 cells. [50][51][52] For example, baculovirus HBV chimeras were used to evaluate the antiviral properties of a nucleoside analog (lamivudine) on HBVreplication in HepG2 cells.…”
Section: Studies Of Viral Infectionsmentioning
confidence: 99%